2021
DOI: 10.1107/s0108767321092072
|View full text |Cite
|
Sign up to set email alerts
|

An ER translocon for multi-pass membrane protein biogenesis

Abstract: Membrane proteins with multiple transmembrane domains play critical roles in cell physiology, but little is known about the machinery coordinating their biogenesis at the endoplasmic reticulum. Here we describe a ~ 360 kDa ribosome-associated complex comprising the core Sec61 channel and five accessory factors: TMCO1, CCDC47 and the Nicalin-TMEM147-NOMO complex. Cryoelectron microscopy reveals a large assembly at the ribosome exit tunnel organized around a central membrane cavity. Similar to protein-conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Conversely, WT interactions peaked at the 0 hr time point and consistently tapered off for many of these components, with DNAJC3 and SDF2L1 mainly being enriched at the 0 hr time point (Figure 3D; Figures S3 and S4). We even noticed altered temporal interactions for previously unidentified components including EMC1 and EMC4 of the ER membrane complex (EMC) and CCDC47 of the PAT complex, all of which are involved membrane protein processing within the ER (Figures 3E; Figure S4) (Chitwood and Hegde, 2020; McGilvray et al, 2020a; Shurtleff et al, 2018). WT Tg interactions with both CCDC47 and EMC1 peak at the end of the chase period, yet for C1264R this temporal profile is inversed peaking at the 0 hr time point and slowly tapering off.…”
Section: Resultsmentioning
confidence: 85%
“…Conversely, WT interactions peaked at the 0 hr time point and consistently tapered off for many of these components, with DNAJC3 and SDF2L1 mainly being enriched at the 0 hr time point (Figure 3D; Figures S3 and S4). We even noticed altered temporal interactions for previously unidentified components including EMC1 and EMC4 of the ER membrane complex (EMC) and CCDC47 of the PAT complex, all of which are involved membrane protein processing within the ER (Figures 3E; Figure S4) (Chitwood and Hegde, 2020; McGilvray et al, 2020a; Shurtleff et al, 2018). WT Tg interactions with both CCDC47 and EMC1 peak at the end of the chase period, yet for C1264R this temporal profile is inversed peaking at the 0 hr time point and slowly tapering off.…”
Section: Resultsmentioning
confidence: 85%
“…3A)(32,33). Multi-pass transmembrane proteins are imported into the ER with the aid of the Nicalin-TMEM147-NOMO complex(34). Numerous proteins within the S1R interactome function at various steps in the ER translocation process (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ile133 is located at the beginning of a-helix 5 between the transmembrane domains 3 and 4, while Arg166 is located at the beginning of a-helix 6 where the transmembrane region initiates (Figure S1). The 3D structure of the translocon was recently resolved by cryo-electron microscopy (PDB: 6W6L, Figure 3A) 9 and used here to further explore the possible functional impact of the three missense changes (Figures 3B and 3C). Considering the p.Gly7Arg substitution, the arginine extension was predicted to push into the TMCO1-facing amino terminal region, creating a steric conflict with the Phe96 (Figure 3, insert 2, asterisks).…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%
“…7,8 A recent study identified a 360 kDa ribosome-associated complex comprising the core Sec61 (translocon) channel and the five accessory factors, transmembrane and coiledcoil domains 1 (TMCO1), coiled-coil domain-containing protein 47 (CCDC47), and the nicalin-TMEM147-NOMO complex, localized at the ribosome exit tunnel, organized around a central membrane cavity revealed by cryo-electron microscopy. 9 The translocon is a highly conserved multi-subunit protein complex that consists of three subunits (Sec61a, Sec61b, and Sec61g) functioning as a protein-conducting channel connecting the cytoplasmic and luminal spaces on either side of the ER membrane. Within the translocon, pathogenic variants involved in a human disease have so far only been identified in SEC61A1 (MIM: 609213), which encodes one of the Sec61a subunits of the translocon complex, generating an autosomal-dominantinherited condition named tubulointerstitial kidney disease 5 (MIM: 617056), responsible for nephropathy with ID.…”
mentioning
confidence: 99%